2003
DOI: 10.1002/ijc.11273
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value ofERBBfamily mRNA expression in breast carcinomas

Abstract: The ErbB-driven autocrine growth pathway has been implicated in the development and progression of most common human epithelial malignancies; its blockade is therefore a promising therapeutic strategy, and several candidate drugs are currently undergoing clinical trials. Paradoxically, little is known of the expression pattern of these 4 genes in human tumors, and the clinical significance of the 2 most recently discovered ERBB genes, ERBB3 and ERBB4, is unclear. We used a real-time quantitative RT-PCR assay t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
170
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 45 publications
14
170
2
1
Order By: Relevance
“…Most metastatic breast cancers show expression for either EGFR or erbB2, and less often for both (Grupka et al, 2004). In contrast, coexpression of erbB3 and erbB2 is frequently observed in breast cancers (Bieche et al, 2003) and cell lines (deFazio et al, 2000). It has been reported that erbB2 requires erbB3 to promote breast cancer cell proliferation (Holbro et al, 2003); and erbB3 has a critical role in erbB2 altered breast cancers (Lee-Hoeflich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most metastatic breast cancers show expression for either EGFR or erbB2, and less often for both (Grupka et al, 2004). In contrast, coexpression of erbB3 and erbB2 is frequently observed in breast cancers (Bieche et al, 2003) and cell lines (deFazio et al, 2000). It has been reported that erbB2 requires erbB3 to promote breast cancer cell proliferation (Holbro et al, 2003); and erbB3 has a critical role in erbB2 altered breast cancers (Lee-Hoeflich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Grb7 is an especially promising cancer target as the encoding gene maps closely to the ErbB2 gene on human chromosome 17q12 and is found co-amplified and overexpressed in a subset of breast, esophageal and gastric cancers (Stein et al, 1994;Kishi et al, 1997;Tanaka et al, 1997;Fiddes et al, 1998;Kauraniemi et al, 2001;Varis et al, 2002;Andrechek et al, 2003;Bieche et al, 2003). Analysis of chromosome 17q12 in a variety of different breast cancer cell lines Grb7 was found to have a high DNA copy number with a high level of ErbB2 co-expression (Kauraniemi et al, 2001).…”
mentioning
confidence: 99%
“…Similar findings were observed in ErbB2-induced mammary tumours from transgenic mice (Andrechek et al, 2003). In addition, Grb7 expression had the strongest association with ErbB2 expression in 54 primary breast tumours analysed by real-time quantitative RT-PCR (Bieche et al, 2003). Co-expression of Grb7 with ErbB2 was detected in 31% of esophageal carcinomas and was significantly correlated with extramucosal tumour invasion (Tanaka et al, 1997).…”
mentioning
confidence: 99%
“…ER is present in epithelial and nonepithelial mammary cells, increasing in hyperplasias (Lee et al, 2006). In addition, reduction in ER and, more radically, PR transcripts in NRLTGFa mice parallels clinical findings in which breast cancers expressing TGFa and ErbB1 had reduced ER (Bieche et al, 2003).…”
Section: Discussionmentioning
confidence: 54%